A Research Machine - Schmidgen, Henning (Helmholtz Curves, 2014)
Let us, therefore, go back to the beginning. This beginning does not correspond to a point but to a “tangle,” a “multilinear ensemble” in whichalllines—not just the lines of art but the lines of technology also—are “subject to changes in direction, bifurcating and forked.”² The winter of 1849–50 was Helmholtz’s first winter in Königsberg. Together with his wife Olga, he had moved from Potsdam to the city of Kant at the end of August to become Ernst Brücke’s successor at the university there. After his studies in medicine under Johannes Müller in Berlin, Helmholtz had